PENGGUNAAN INFORMATION GAP ACTIVITY UNTUK PENINGKATAN KEMAMPUAN BERBICARA SISWA PADA PEMBELAJARAN BAHASA INGGRIS to Improve Students’ Speaking Ability in English - Osra, Desniza (Balai Bahasa Sumatra Barat, 2015)
The problem of this research is the low of students’ speaking ability of class VIIID in learning English at SMP Negeri 8 Padang. The purpose of this research is to improve students’ abilityin learning English at SMP Negeri 8 Padang. This research used classroom action research in two cycles. Every cycle is done in three meetings and through planning, action, observing andreflection. The data are collected by using speaking test and supported by direct observation by collaborator teacher as an observer through observation sheet and interview for aTriangulation process for accurate data. The learning activity used Information Gap Activity is imprÅ¿ßO• —nî?;ßO•—nðinitial condition to 70% in final condition, increased 25%. The resultof students’ score is also increased from the average of 78,80 in initial process became 81,00 in final condition, increased 2,20 point. The improvement can only be seen from the result ofthe score, but also form the students’ activeness and motivation in the process of learning recorded from the data of observation and the result of students’ interview, so it can be concluded that the use of Information Gap Activity can improve the students’ speaking ability of class VIID at SMP Negeri 8 Padang in learning English.